Analisa Strategi E-Marketing Untuk Meningkatkan Minat Beli Online - Dewi Wulansari; Dody Tri Kurniawan; Iddrus Iddrus (CV. Aksara Global Akademia, 2024)
Kitchen equipment businesses have done for a long time in Indonesia, both it managed by offline and online. However, recently there are some businesses that used online transactions. Internet facilities provide the business opportunities develop more quickly, there are many who begin with a simple concept and there is a few who are close to being professional. Sometimes, the using of e-commerce is less than optimal because of poor management, such as poor web appearance, less attractive writing, do not including current promotional language, the pricing strategies and product descriptions that are less in detailed. In general, this is a lack of online marketing activities on existing e-commerce media. This situation provides an idea for the researchers to conduct a research to analyze the people's buying interest in e-commerce that sell kitchen equipment products in Sumenep and their strategies.This research was conducted by distributing some questionnaires at several locations in Sumenep with the priority targets are house wives which the results will be explained descriptively. This strategy analysis using SWOT analysis tool.